Regulation by Rab3A of an endogenous modulator of neurotransmitter release at mouse motor nerve endings - Hirsh, Jody K (Blackwell Science Inc, 2002)
Rab3A, a small GTP-binding protein attached to synaptic vesicles, has been implicated in several stages in the process of neurosecretion, including a late stage occurring just prior to the actual release of neurotransmitter. The inhibitory neuromodulator adenosine also targets a late step in the neurosecretory pathway. We thus compared neuromuscular junctions from adult Rab3A(−/-) mutant mice with those from wild-type mice with respect to: (a) the basic electrophysiological correlates of neurotransmitter release at different stimulation frequencies, and (b) the actions of exogenous and endogenous adenosine on neurotransmitter release in normal calcium solutions. Neither the spontaneous quantal release of acetylcholine (ACh) nor basal evoked ACh release (0.05 Hz) differed between the mutant and wild-type mice. At 50-100 Hz stimulation (10-19 stimuli), facilitation of release was observed in the mutant mice but not in wild-type, followed by a depression of ACh release in both strains. ACh release at the end of the stimulus train in the mutant mouse was approximately double that of the wild-type mouse. The threshold concentration for inhibition of ACh release by exogenous adenosine was over 20-fold lower in the mutant mouse than in the wild-type mouse. The adenosine A(1) receptor antagonist 8-cyclopentyltheophylline (CPT) increased ACh release (0.05-1 Hz stimulation) in the mutant mouse under conditions in which it had no effect in the wild-type mouse. CPT had no effect on the pattern of responses recorded during repetitive stimulation in either strain. The results suggest that Rab3A reduces the potency of adenosine as an endogenous mediator of neuromuscular depression.